Geographical Analysis of Trends in the Phenomenon of Suicide in the Municipality of Misurata (Abhat Journal, 2023)
The study aims to geographically analyze the phenomenon of suicide in the municipality of Misurata, and to identify the underlying motives behind the high rates of suicides, in addition to studying their geographical distribution according to the municipal branches, and studying their qualitative and age structure.       The study used the descriptive approach to study the phenomenon and describe its spatial and temporal distribution, in addition to Using the analytical method to analyze and compare the data, the study concluded that there is a group of economic, social and psychological reasons that have combined to form a motive towards suicide, and that suicide cases during the period from 2015-2022 have reached (110) cases, and that the municipalbranch of Shuhada al-Rumaila may issue the rest The municipal branches accounted for (17) suicide cases, which constitutes (15.4%), and constitutes (2.7) suicide cases for every (10,000) inhabitants of the total population of the municipal branch, Shuhada Al-Rumaila. Females, where the total number of suicides among males reached (97) cases, while it did not exceed (13) cases among females. In addition to the increase in the number of suicides among young people (18-64) years, as it reached (102) suicide cases, compared to (7) cases among young people under (18) years, and one suicide case among adults (65 and over).
Keywords: Suicide; geographical distribution; Social Structure; Suicide motives; qualitative Structure.